Determinants of Persistent Organic Pollutants (POPs) Levels in Human Specimens: A Review - Farah Zahira; Kusuma Scorpia Lestari; Ahmad Zaharin Aris (Universitas Airlangga, 2021)
Introduction: Numerous studies have been conducted regarding persistent organic pollutants (POPs) concentrations in human biological matrices such as blood, breast milk, urine, and hair that cause adverse health effects such as breast cancer, cardiovascular diseases, and type 2 diabetes. This study aimed to determine the POPs presence in human specimens in household settings. Discussion: A total of 28 articles were included in this study with the criteria published in 2016- 2021, original research articles, free full text available, and studied at least one of the confounding variables of POPs levels in human specimens. The narrative method was selected to synthesize this study. Grouping articles with similar results was carried out to respond to research questions. This study discovered that age, dietary habits, BMI, sex, race/ethnicity, smoking status, physical activities, residency, household dust, and industry emissions were associated with POPs levels in human specimens. Conclusion: This study concluded that each determinant could not affect the POPs levels in the human specimens on its own since those determinants are influenced by each other. Future research using systematic literature review and meta-analysis is therefore strongly advised.